Effect of Alfalfa Hay and Starter Feeding Intervention on Gastrointestinal Microbial Community, Growth and Immune Performance of Yak Calves - Cui, Zhanhong; Wu, Shengru; Li, Jilan; Yang, Qi-En; Chai, Shatuo; Wang, Lei; Wang, Xun; Zhang, Xiaowei; Liu, Shujie; Yao, Junhu (Frontiers in Microbiology, 2020)
The present study aims to evaluate the effects of different early weaning paradigms, which supplied with extra alfalfa hay, or starter feeding, or both alfalfa hay and starter feeding, along with the milk replacer, on the gastrointestinal microbial community, growth, and immune performance of yak calves. Twenty 30-day-old male yak calves were randomly assigned to four groups, including the control (CON), alfalfa hay (A), starter feeding (S), and starter plus alfalfa hay (SA) groups. The gastrointestinal microbial colonization, the gastrointestinal development and function, and the growth and immune performance of all the yak calves were separately measured. Supplementation with alfalfa and starter feeding during the pre-weaning period significantly increased body weight, body height, body length, and chest girth. The significantly improved rumen fermentation and promoted intestinal digestion-absorption function in alfalfa and starter feeding groups, including the identified significantly increased concentrations of ruminal total volatile fatty acid (VFA); the significantly increased concentrations and proportions of acetate, butyrate, and isovalerate; the increased α-amylase activities in the duodenum, jejunum, and ileum; the increased papillae length and width of rumen epithelium and rumen wall thickness; and the increased villus height and crypt depth of the duodenum, jejunum, and ileum, could all contribute to promote the growth of calves. These significant improvements on rumen fermentation and intestinal digestion-absorption function could be further attributed to the increased proliferation of starch-decomposing, and cellulose- or hemicellulose-decomposing bacteria identified in the rumen, jejunum, and ileum. Furthermore, based on the expression of intestinal inflammatory cytokines and the rumen epithelial RNA sequencing results, alfalfa supplementation reduced the occurrence of ruminal and intestinal inflammation, whereas starter feeding supplementation was mainly beneficial to the differentiation of immune cells and the improved immune function. Meanwhile, the significantly altered relative abundances of genera in the SA group, including increased relative abundance of Limnobacter, Escherichia/Shigella, and Aquabacterium in the rumen and increased relative abundance of Coprococcus, Pseudobutyrivibrio, Flavonifractor, Synergistes, and Sutterella in jejunum, were able to reduce gastrointestinal inflammation and enhance the immune function, which enhanced the immune function of the yak calves fed with alfalfa and starter feeding. Overall, milk replacer supplemented with alfalfa and starter feeding during the pre-weaning period could alter gastrointestinal microbiota and then benefit the gastrointestinal development, digestion-absorption function, growth, and immune performance of the yak calves.